Methods for Maintaining Insect Cell Cultures - Lynn, Dwight E. (University of Arizona Library, 2002)
Insect cell cultures are now commonly used in insect physiology, developmental biology, pathology, and molecular biology. As the field has advanced from methods development to a standard procedure, so has the diversity of scientists using the technique. This paper describes methods that are effective for maintaining various insect cell lines. The procedures are differentiated between loosely or non-attached cell strains, attached cell strains, and strongly adherent cell strains.